Investigation of the Turkey’s Climate for Service Lifetime of Photovoltaic Modules: A Mapping Approach - Gok, Abdulkerim (My University, 2023)
The longevity of photovoltaic systems during real-world operation is a concern that needs to be addressed. Polymeric materials used in module constructions, particularly encapsulants, are susceptible to hydrolysis, which can lead to cell metallization corrosion and result in power loss and shortened service lifetime. One of the test protocols within the current certification standard of IEC 61215 is damp heat exposure, which subjects the modules to constant temperature and humidity level for a specific duration (85°C/85%RH for 1000 hours). However, its effectiveness as a reliability test for long-term durability is often debated. This study applies a methodology for calculating the equivalent damp heat testing time that corresponds to a targeted service lifetime (i.e., 30 years) in real-world conditions. The results are presented in the form of a country map, focusing on Turkey, illustrating the variations in testing times across different regions due to local climate conditions. This study shows that applying a single set of conditions for a fixed duration, as applied in the damp heat testing, to all modules with different components and for all climate conditions poses substantial risks when it comes to predicting service lifetime.
Keywords: Reliability; Degradation; PV Modules; Standard Testing; Service Lifetime